Sixteen years later: an updated evaluation of the impacts of chronic human interactions with bottlenose dolphins (Tursiops truncatus truncatus) at Panama City, Florida, USA - R. Powell, Jessica; F. Machernis, Abigail; K. Mullen, Laura; A. Farmer, Nicholas; R. Spradlin, Trevor (J. Cetacean Res. Manage., 2023)
Panama City, Florida is considered a notorious ‘hot spot’ in the southeastern United States for chronic illegal feeding and harassment of bottlenose dolphins. The nature and extent of these interactions was evaluated by Samuels and Bejder (2004); they concluded that food provisioning was the basis for human interactions with wild dolphins, and that these encounters were likely harmful to dolphins. A follow-up study was conducted in 2014 to reassess the current state of human interactions with wild dolphins. The number of conditioned dolphins (n = 21) tripled compared to the previous study. Both studies found conditioned dolphins engaged in human interaction events during approximately 75% of observable time points when vessels or swimmers were present. In this study, conditioned dolphins spent as much as 81% of their time begging or patrolling and significantly decreased their distance moved while doing so. Nested multinomial regression analysis revealed conditioned dolphins engaged in resting or foraging (i.e. natural) behaviour were extremely likely to switch to begging or patrolling (i.e. interaction) behaviours when vessels or swimmers were present. Numerous high risk situations were observed for both conditioned dolphins and humans during these interactions. The latest development in illegal feeding was documented: bait boats feeding dolphins to lure the animals into interactions with tour vessels and swimmers. Our observations indicate that the problem in Panama City has escalated: dolphins are being actively provisioned, often for long periods of time; the proportion of conditioned dolphins has increased; interacting dolphins and humans are both at increased risk for injury, illness, or death; and conditioned dolphin activity budgets and movement patterns continue to be negatively impacted by human behaviour. We recommend a more aggressive management strategy, such as targeted and sustained enforcement of existing regulations as well as additional restrictions that prohibit close approaches and in-water interactions for Panama City in order to curtail continued harassment of dolphins and reduce the risk of injury for both humans and dolphins.